Effects of nanoindents on the martensitic transformation of Ni-Mn-Ga shape-memory Heusler films: A study by high-resolution imaging as a function of temperature. (15th February 2023) - Takhsha Ghahfarokhi, M.; Casoli, F.; Minnert, C.; Bruns, S.; Bruder, E.; Cabassi, R.; Durst, K.; Gutfleisch, O.; Albertini, F.
Abstract: Nanoindentation was used to analyze the effect of localized plastic deformation on the martensitic transformation of epitaxial Ni-Mn-Ga films on MgO(001) substrate. Atomic and magnetic force microscopy imaging at elevated temperature was applied to study the martensitic transformation route from the nanometer to the micrometer scale. We analyzed the cooling and heating curves for the martensitic transformation of the nanoindented areas as a function of the applied loads as well as the distance from the material pile-ups around the residual impressions. We observe a thermodynamically governed local increase of the martensitic transformation temperature (i.e. martensite stabilization) as a function of the applied loads. The local increase of the transformation temperature vs . the applied load ( P ) follows a non-linear regime: reducing the slope by increasing the applied load and showing a plateau for P ≥ 5 mN. The observed effect is local and almost disappears for distances larger than 500 nm from the pile-ups around the residual impressions, where the material transforms similar to the pristine sample. The local increase of transformation temperature as a function of nanoindentation loads is the dominant effect and occurs in both the cooling and the heating curves. Therefore, no considerable thermal hysteresis variation is observed in the transformation of the material. Moreover, we report in average ∼12% higher relative areal shift of the transformation curves over cooling than heating close to the indents reflecting an unequal impact of indents on T M and T A in Ni-Mn-Ga. Graphical abtract: Image, graphical abstract